2019
DOI: 10.1080/17430437.2019.1599201
|View full text |Cite
|
Sign up to set email alerts
|

Composite vignettes of Swedish male and female professional handball players’ career paths

Abstract: The aim of this study was to describe gender-specific career paths of Swedish professional handball players. A reanalysis of Ekengren et al. (2018) career interviews with nine male and nine female players led to creating two composite vignettes using the athletes' own words, accounted for typical features in the male and female players' career paths. Seven themes were identified in the analysis of the men's transcripts and eight themes derived from the women's transcripts. Further, the themes of both vignettes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
15
1
1
Order By: Relevance
“…Regarding the mastery stage, in handball 20 and in NHL, 21 it was highlighted that the mastery stage is characterized by four major career stages related to the level of performance of practice (i.e. access to semi-professional or professional sport, developing as a professional player, reaching the elite, and maintaining the professional status).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the mastery stage, in handball 20 and in NHL, 21 it was highlighted that the mastery stage is characterized by four major career stages related to the level of performance of practice (i.e. access to semi-professional or professional sport, developing as a professional player, reaching the elite, and maintaining the professional status).…”
Section: Introductionmentioning
confidence: 99%
“…Both studies reinforce that the mastery stage lies between the normative transitions from junior to senior and retirement and integrates different non-normative transitions that players face during their senior career. 20 During all the stages, and particularly in the mastery stage, the athletic path is nonlinear and subtle changes in the career development could potentiate unexpected career paths. 18 Likewise, it was stated that career pathways were not consciously defined along with the career 12 and did not consider a previous plan of development, in line with the reported in football.…”
Section: Introductionmentioning
confidence: 99%
“…We also relied on good practice examples from career assistance literature (e.g., Torregrossa et al, 2020). These mentioned models and frameworks were combined with major findings from our research project on career development in Swedish handball (Ekengren et al 2018;Ekengren, Stambulova, Johnson, Carlsson, et al 2020) to heuristically develop the initial version of the CPS-H. The first sketch of the CPS-H was discussed, challenged, and revised several times within the author group until we were basically satisfied with the structure.…”
Section: Reflections and Recommendationsmentioning
confidence: 99%
“…We started the project by studying (whole) career experiences of Swedish handball players (Ekengren et al 2018;Ekengren, Stambulova, Johnson, Carlsson, et al 2020), proceeded with development and validation of the career-long psychological support system (from now the CPS-H) in Swedish handball (i.e., the focus of this paper), which then was tested in (so far) one intervention study (Ekengren, Stambulova, Johnson, Ivarsson, et al 2020).…”
mentioning
confidence: 99%
“…Other scholars have alerted us to the effects of neoliberal understandings that hold the individual solely responsible for navigating the demands of education and career (Brunila et al 2011;Holmegaard, Ulriksen, and Madsen 2014;Leccardi 2014;Pless 2014) and instead emphasise the role of the cultural and discursive contexts in athletes' ability or inability to plan for the future (Cosh, Crabb, and Tully 2015;Ronkainen and Ryba 2018;Ryba and Wright 2010;Skrubbeltrang 2018;Skrubbeltrang et al 2018). It has been suggested that young peoples' aspirations are influenced by narratives of gender (Ekengren et al 2019;Skrubbeltrang 2018) and age (Henriksen and Mortensen 2014) as well as by the dominant belief systems, values, practices, and policy discourses that circulate in their national contexts (Leccardi 2014;Pless 2014).…”
Section: Introductionmentioning
confidence: 99%